Peklenski hrup ob prepovedi izdelkov - Eagle, Lynne (Teorija in praksa, 2007)
Medicines, in their various forms, are an important part of daily life and health for many consumers across diverse cultures. However, beliefs and trust inherent in treatment are - at best - poorly understood. Major dislocation of trust occurs when the media report medical scandals, or when there are major health scares such as product contamination and mandatory product recalls. Themid-2003 government-ordered withdrawal of almost 2,000 complementary and alternative medicines, across multiple brand names in the Australian and New Zealand markets provides an opportunity to examine the impact on both the wide complementary and alternative medicines category and on brand sales and brand equity issues for both affected and unaffected brands. We focus on the impact of these events within the New Zealand market, and link the events surrounding the recall with the somewhat scant crisis management literature and report on consumer perceptions of the sector six months after the recall event. We then offer conclusions and recommendations for the management of such events across national boundaries in the future.
Keywords: Marketing communication; Tržno komuniciranje; Zdravila; Medicaments; drug; blagovne znamke; potrošniki; krizni management